2010
DOI: 10.1371/journal.pgen.1000903
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA–Directed siRNA Biogenesis in Caenorhabditis elegans

Abstract: RNA interference (RNAi) is a post-transcriptional silencing process, triggered by double-stranded RNA (dsRNA), leading to the destabilization of homologous mRNAs. A distinction has been made between endogenous RNAi–related pathways and the exogenous RNAi pathway, the latter being essential for the experimental use of RNAi. Previous studies have shown that, in Caenorhabditis elegans, a complex containing the enzymes Dicer and the Argonaute RDE-1 process dsRNA. Dicer is responsible for cleaving dsRNA into short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 40 publications
(53 reference statements)
13
63
0
Order By: Relevance
“…A third member, RDE-1, is involved in the double strand RNA-induced siRNA pathway (Tabara et al 1999). Consistent with the previous report (Corrêa et al 2010), most of the reads bound to these Argonaute proteins were found to be miRNAs. Notably, we found that the miRNA reads corresponding to star strands were significantly enriched in the RDE-1 ChIP-Seq library compared to those in ALG-1 or ALG-2 (Supplemental Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A third member, RDE-1, is involved in the double strand RNA-induced siRNA pathway (Tabara et al 1999). Consistent with the previous report (Corrêa et al 2010), most of the reads bound to these Argonaute proteins were found to be miRNAs. Notably, we found that the miRNA reads corresponding to star strands were significantly enriched in the RDE-1 ChIP-Seq library compared to those in ALG-1 or ALG-2 (Supplemental Fig.…”
Section: Resultssupporting
confidence: 88%
“…Additionally, the accumulation of star miRNAs as well as mature ones was reduced in rde-1 mutants compared to wild-type animals (Supplemental Fig. S7B; Supplemental Table S7) (sequence data were obtained from GEO, accession: GSE20649) (Corrêa et al 2010). A similar reduction of miRNA star level in rde-1 mutants was also observed in another library obtained from the GEO, GSE19414 (Gent et al 2010) (data not shown).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Again in agreement with previous work (Corrêa et al 2010), we did not observe a direct correlation between expression level of genes in rde-1 mutants and reduced antisense small RNA reads. However, 5% of the genes showing robustly reduced antisense small RNA reads in rde-1 mutants also showed >30% increased expression in rde-1 mutants relative to N2.…”
Section: Regulation Of Viral Response Genes By Rde-1supporting
confidence: 93%
“…Although most miRNAs are associated with the Argonaute proteins ALG-1 and ALG-2, certain miRNAs have been shown to bind to RDE-1 (Corrêa et al 2010). However, in agreement with this study, we did not find a clear difference in overall read counts of these miRNAs in rde-1 mutants, nor in the expression of predicted target genes of these miRNAs upon infection of N2 (data not shown).…”
Section: Regulation Of Viral Response Genes By Rde-1supporting
confidence: 89%